Antineoplastic activity of linear leucine homodipeptides and their potential mechanisms of action. Issue 6 (July 2018) - Lei, Yun; Yang, Xiao-Xia; Guo, Wei; Zhang, Fu-yong; Liao, Xiao-Jian; Yang, Hui-Fu; Xu, Shi-Hai; Xiong, Sheng
Abstract : Galaxamide is a rare cyclic homopentapeptide composed of three leucines and two N -methyl leucines isolated from marine algae Galaxaura filamentosa . The strong antitumor activity of this compound makes it a promising candidate for tumor therapy. The synthesis of galaxamide, however, is a complex process, and it has poor water solubility. On the basis of its special chemical composition, we designed a series of linear leucine homopeptides. Among seven dipeptide derivatives, five compounds with terminal protection groups and methyl substitution of the hydrogen in the amido group showed remarkable inhibitory effects against various cancer cells. N -tertbutyl-D-leucine- N -methyl-D-leucinebenzyl (A7), the only stereomer condensed by two D-leucines, showed the highest antineoplastic activity. A7-treated cells showed cell cycle arrest and morphological changes typical of cells undergoing apoptosis. The population of Annexin-V positive/propidium iodide-negative cells also increased, indicating the induction of early apoptosis. A7 promoted the cleavage of caspase-9 and caspase-3, as well as increased intracellular Ca 2+ levels and decreased the mitochondrial membrane potential. Collectively, certain linear leucine dipeptides derived from cyclic pentapeptide are able to inhibit tumor cell proliferation through cell cycle arrest and apoptosis induction. The N -methyl group in the side chain and the D/L conformation of the amino-acid residue are critical for their activity. Abstract : Supplemental Digital Content is available in the text.